Structural characterization and pharmacological assessment in vitro/in vivo of a new copper(ii)-based derivative of enrofloxacin. Issue 12 (10th December 2020) - Guo, Rui-Feng; Yan, Hou-Tian; Liu, Rui-Xue; Li, Hong-Chang; Liu, Yan-Cheng; Chen, Zhen-Feng; Liang, Hong
Abstract : A new copper(ii ) complex of enrofloxacin showed wide-spectrum and comparable antibacterial activity to enrofloxacin in vitro, but much lower acute toxicity in mice in vivo, suggesting a promising veterinary substitute for enrofloxacin. Abstract : Enrofloxacin (EFX) was selected as the medicinal ligand to afford a new copper(ii )-based complex, EFX-Cu, which was structurally characterized by spectroscopic analyses including X-ray single crystal diffraction. It was also stable and could retain the coordination state in aqueous solution. The in vitro antibacterial activity of EFX-Cu against a panel of pathogenic bacteria was about the same as that of EFX, except that it was twice as active against E. coli . The in vivo test on mice gave a LD50 value of 8148 mg kg −1 for EFX-Cu, which was much lower than those for EFX (LD50, 5312 mg kg −1 ) and its clinically used sodium salt, EFX-Na (LD50, 1421 mg kg −1 ). In addition, no obvious lesions in the organs of the dead mice were found by histopathological examination. Pharmacokinetic studies on rats suggested similar pharmacokinetics between EFX-Cu and EFX. On the other hand, EFX-Cu showed higher acute toxicity than EFX-Na in zebrafish, which was inconsistent with that in mice. The ROS-related inflammation and anti-inflammatory assay of EFX-Cu, respectively, in normal cells and zebrafish could be ascribed to its ROS-related redox property. Unfortunately, the final in vivo therapeutic assay in the E. coli -infected mouse model indicated that the therapeutic effect of EFX-Cu, mainly in terms of mortality in mice, was found to be lower than that of EFX-Na at the same dosage (800 mg kg −1, continuous gavage), although the contradictory factors between toxicity and antibacterial activity could not be excluded in this trial.